UPAYA PENYELESAIAN SENGKETA BISNIS MELALUI ADR (ALTERNATIF DISPUTE RESOLUTION) DI DESA GIRI MADIA KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - I GUSTI AGUNG WISUDAWAN; H. MOH SALEH; EDUARDUS BAYO SILI; DIMAN ADE MULADA (SOSIAL SAINS DAN TEKNOLOGI, 2023)
Currently, business activities have grown very rapidly, this is supported by the application of super-sophisticated information technology. Business activities include production, distribution, consumption, business contracts and international trade. It is undeniable that in carrying out business activities there are disputes. Dispute is a discrepancy between the will of one legal subject with another legal subject on something. In the Indonesian Constitution and Pancasila, it is regulated about deliberation for consensus as an alternative dispute resolution which is then adopted in the form of ADR (Alternative Dispute Resolution) as regulated in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This legal counseling activity aims to provide education, knowledge and understanding to the people of Giri Madia Village, Lingsar District, West Lombok Regency in order to resolve business disputes through ADR so as to achieve legal justice for the parties with the principle of Win-Win Solution